2019
DOI: 10.1111/tbj.13425
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of ductal carcinoma in situ of the breast: A large retrospective study from a single institution

Abstract: Background Management of breast ductal carcinoma in situ (DCIS) has various approaches with distinct institutional specific practice. Here, we review DCIS management in a single institution with emphasize on re‐operation rates and outcome. Methods Breast ductal carcinoma in situ cases diagnosed at the Nottingham Breast Institute between 1987 and 2017 were identified (n = 1249). Clinicopathological data were collected. Cases were histologically reviewed, and different factors associated with primary operation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…These findings were addressed in our previous work using on the same cohort which where we showed lower rates of high risk DCIS over the time which was reflected by higher rate of BCS as a primary surgical management, lower rate of second operation 27 and decrease the proportion of HER2 positive DCIS over time 29 . Moreover, the protocol for management of DCIS in routine practice changed over the time.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…These findings were addressed in our previous work using on the same cohort which where we showed lower rates of high risk DCIS over the time which was reflected by higher rate of BCS as a primary surgical management, lower rate of second operation 27 and decrease the proportion of HER2 positive DCIS over time 29 . Moreover, the protocol for management of DCIS in routine practice changed over the time.…”
Section: Discussionmentioning
confidence: 79%
“…Management details including the operation type (BCS or mastectomy), and RT data were collected. Over the period of the study, the management of DCIS showed significant changes with an increase in rate of BCS over mastectomy, and more frequent use of local RT as previously described 27 . ER status was not routinely assessed in DCIS unless indicated for diagnostic purposes and was not used to guide further management.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…We previously found that CD4+ and CD8+ TILs are correlated with a favorable prognosis in triple-negative breast cancer (TNBC) [11]. Although the prognostic correlation of TILs-T has been widely reported, there are few studies on infiltrating B lymphocytes (TILs-B) in breast cancer and there is no consensus on their prognostic impact [12][13][14][15][16][17][18][19][20]. In addition, few studies have investigated TILs-B and TILs-T in combination [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%